Aspek dan Simtom Kecemasan Sosial pada Tokoh Utama Komi Shouko dalam Manga Komi-San Wa, Komyushou Desu Karya Tomohito Oda - Atarik, Jalu Muhammad; SS., M.Pd, Novi Andari (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2023)
Social anxiety is excessive fear and worry when someone is with other people and feels anxious in social situations. The main character featured in the manga Komi-san wa, Komyushou desu shows behavior that is allegedly a symptom of social anxiety disorder which is influenced by 3 aspects namely fear of negative evaluation, social avoidance and distress new, and social avoidance and distress general and characterized by 3 symptoms, namely somatic symptoms, cognitive and emotional symptoms, and behavioral symptoms. The purpose of this study was to find out what aspects influence social anxiety and to find out the description of the symptoms of social anxiety in the main character Komi Shouko. This study uses a descriptive qualitative method with a psychological approach. From the research that has been done, it is concluded that there are symptoms of social anxiety disorder experienced by Komi Shouko, and of the three symptoms, Komi Shouko dominantly shows behavioral symptoms as an attempt to hide reactions from cognitive and emotional symptoms, and somatic symptoms. And in terms of aspects, Komi's social anxiety is more influenced by aspects social avoidance and distress new and general, because they feel pressured towards new or unfamiliar people or in public places, and avoidance to calm down.